A stochastic micro-machine inspired by bacterial chemotaxis. (10th November 2016) - Mohammadi, Hossein; Esckandariun, Banafsheh; Najafi, Ali
Abstract: Inspired by bacterial chemotaxis, we propose and study the dynamics of a 3D hydrodynamical search-machine at micrometer scale. Chemotactic memory of the proposed system that is borrowed from bacteria, allows it to search the fluid medium and find the required target. As the motion in micron size length scale is dominated by random forces, we analyze the statistical properties of the model. Mean square displacements, orientational correlation functions and also the chemotactic index (CI) of the system are investigated in detail. Because of the chemotactic memory, the system shows superdiffusing displacements in all directions and the diffusion exponents are anisotropic for the directions along or perpendicular to a preferred direction given by the gradient of attractant molecules transmitted by the target.